Senior High School Strands: Factors Affecting the Students’ Preference - Malaguial, Princes Aires; Gacoscos, Goji; Martinez, Edward; Abusama, Hassanal; Valdez, Anamarie (Bumi Publikasi Nusantara, 2023)
Choosing a senior high school strand is one of the most challenging decisions that junior high school students will have to face. The study aimed to help students decide on their future senior high school strand by knowing the factors’ influence levels and their relationship with their decision. The survey was conducted online (Grade 9 and Grade 10 students) using the total sampling method. We employed a self-made questionnaire that went through content validation using Aiken’s V formula. Descriptive statistics were then used to analyze and interpret the results of the study. In the survey’s results, 2.3% of the students chose GAS as their senior high school strand, 15.9% chose HUMSS, and 73.9% chose STEM, leaving the ABM strand with 8%. The personal interest factor had the highest level of influence among the factors, with a mean of 4.21, followed by job opportunities with a mean of 4.17, socioeconomic status with a mean of 3.89, parents with a mean of 3.63, and academic performance with a mean of 3.38. However, in terms of the factors’ significant relationships with the senior high school strands, socioeconomic status, parents, job opportunities, and personal interests were found to have no significant influence when deciding, and academic performance is the only factor that has a significant influence on the students’ preferred strand. As a result, the null hypothesis of the study is accepted because only one out of five factors were found to have a significant relationship when deciding on a senior high school strand.